How the Consumer Confidence Index Affect the Credit Growth in Indonesia? - Alif, Pevi Fitria Kartika; Ajija, Shochrul Rohmatul; Fitriyana, Zidna; Setyorini, Wahyu (Jurnal Ilmu Ekonomi Terapan, 2025)
Credit has a positive role in encouraging economic growth in Indonesia. A factor that can influence the level of credit distribution is consumer confidence in economic conditions. Therefore, this research aims to examine the influence of the consumer confidence index and several other factors, such as inflation, third-party funds, and credit interest rates on commercial bank credit distribution in Indonesia. By using time series data for the period 2008:1-2019:12 and the Ordinary Least Square (OLS) method, this research shows that the level of consumer confidence in Indonesia’s economic conditions has a positive effect on credit distribution. The higher inflation encourages customers to apply for more credit. Apart from that, the high and low levels of credit disbursement were also positively influenced by the amount of third-party funds but were not affected by high or low credit interest rates. Thus, keeping consumer confidence high and inflation under control even though it is increasing, and raising the number of third-party funds is essential so that the economy continues to grow through the transmission of credit lines.